How do you solve p^ { 2} - 12p - 73= 0?
2 Answers
Explanation:
We can solve this by completing the square and using the difference of squares identity:
A^2-B^2 = (A-B)(A+B)
with
0 = p^2-12p-73
color(white)(0) = p^2-2p(6)+36 -36-73
color(white)(0) = p^2-2p(6)+36-109
color(white)(0) = (p-6)^2-(sqrt(109))^2
color(white)(0) = ((p-6)-sqrt(109))((p-6)+sqrt(109))
color(white)(0) = (p-6-sqrt(109))(p-6+sqrt(109))
Hence:
p = 6+-sqrt(109)
Explanation:
Use the quadratic formula.
where
When you plug everything in, you get two answers: